Electric conductivity test for quality assessment of aromatic and medicinal plants after drying. Issue 5 (4th April 2018) - Coradi, Paulo Carteri; Müller, Amanda; Schmidt, Diogo André; Lima, Roney Eloy; Baio, Fábio Henrique Rojo; Borsato, Aurélio Vinícius; Blanco, Matildes
ABSTRACT: For the production of essential oils and aromatics to be possible throughout the year, it is necessary to continuously supply the plant raw material to the industry or store the plant material for a designated time. However, to allow the plant material to remain in storage with a high quality, it is essential to reduce its water content by drying. This has motivated the oil extraction industries to demand a better yield and quality from the drying process and raw materials, necessitating fast and efficient evaluation parameters. Thus, the aim of this study was to develop an electric conductivity test for evaluating the quality of aromatic and medicinal plants and to quantify the essential oil yield of the dry vegetable material. The drying experiments were conducted at different temperatures and air velocities by altering the control of the drying conditions. Various aromatic plants with different plant mass, volume of deionized water, and temperature of the vegetal material were examined by the electric conductivity test. The qualities of the fresh and dry plants were compared through these tests and yields of essential oil. Increase in the drying air temperature influenced the increase in the dehydration rate of the aromatic and medicinal plants. Higher drying temperatures decreased the physical quality as evaluated by the electric conductivity test and essential oil yield of the aromatic and medicinal plants. The parameters for validation of the electric conductivity test methodology in aromatic and medicinal plants were defined as an exposure time of 33 h, 5 g of fresh plant material in 75 mL of deionized water, 1 g of dry plant material in 50 mL of deionized water, and temperature of 25°C. The electric conductivity test was demonstrated as an appropriate method to be used in the quality control of aromatic plants in essential oil extraction industries. The use of the electric conductivity test will enable the oil extraction industry to monitor the yield and quality of the essential oils extracted from the aromatic plants after drying and storage.